Spettri della violenza politica: gli anni Settanta in alcuni romanzi del nuovo millennio (ENTHYMEMA, 2012)
One of the radical changes occurring in the American socio-cultural context during the 1970s concerns the notion of subjectivity and its relationship with political, mediatic, and economic systems, which produce and control subjectivity itself. The counter-culture most extremist drifts and the conservative turning point imposed by Nixon’s presidency led to a conspiratory and paranoid mood. As a result, the critical subject finds itself trapped within broad ramified structures that attempt to dismantle oppressive over-individual powers -either a state or a military power- constantly negotiating its own identity in terms of freedom or antagonism. However, this form of dissent often turns to be a fatuous or lethal effort, and even an unrealizable attempt. Potentialities and limits of this political and cultural self-determination of subjectivity are variously portrayed by 1970s American literature and, in particular, by Thomas Pynchon’s Gravity’s Rainbow. In this text, the post-WWII world, destroyed by the world conflict, epitomizes the intersection of heterogenous plots, amplified by the Cold War and sustained by those technological powers that would explode during the 1970s. In his book, Pynchon summarizes the complexity and ambiguity of the postmodern cultural system wherein individuals, sadically manipulated, find it difficult to conceive a space of freedom or collective form of resistance.